Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation Report : The IMF and Social Protection. (Policy Papers; Policy Paper ;, 2018)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) report on 'The IMF and Social Protection.' The management implementation plan (MIP) proposes specific actions to address the IEO recommendations endorsed by the Executive Board in its discussion on July 19, 2017, specifically to: (i) establish a clear strategic framework to guide Fund involvement in social protection; (ii) provide tailored advice based on in-depth analysis of the particular country situation; (iii) find more realistic and effective approaches to program design and conditionality to ensure that adverse impacts of program measures on the most vulnerable are mitigated; (iv) realistically explain in external communications the IMF's approach to social protection issues; and (v) engage actively in inter-institutional cooperation on social protection to find ways to work constructively with development partners, particularly institutions with different mandates and policy priorities. The MIP notes that the Board underscored the need to be mindful of the Fund's mandate to engage only in macro-critical areas while bearing in mind its resource constraints and comparative expertise in implementing these recommendations. Implementation of some of these proposed actions is already underway. The paper also explains how implementation will be monitored and the MIP's resource implications.